Design, Modeling and Simulation of Microhotplate in Gas Detection Application - Mohd Faisal Baskaran, Fatimah (2017)
In this paper, the modeling and design of the platinum Microhotplate (MHP) for gas sensing applications using Coventorware is presented. The MHP is designed to achieve good temperature uniformity with low power dissipation. The length of MHP microbridges are varied from 120 to 200 while the width of MHP microbridges are varied from 10 to 30 , the effect of the length and width are investigated and the optimized design with microbridges length of 160 and width of 20 is chosen. From the mathematical modeling, the power dissipation and the operating temperature are calculated by applying actuation voltage from 0.25V to 2V. The modeling gives out the power dissipation of MHP from 0.13mW to 8.57mW for operating temperature from 9.5°C to 607.85°C meanwhile the simulation gives out the power dissipation of 0.14mW to 8.71mW for temperature from 9°C to 586.78°C with temperature gradient of the MHP is 4.18°C.